Thrombus-in-Transit: Changing the Diagnosis from Acute Coronary Syndrome to Pulmonary Embolism - Muhammad Mohsin, Khawar Naeem Satti, Muhammad Saleem, Naveed Yaqoob (Journal of Rawalpindi Medical College, 2018)
Pulmonary embolism is a disease entity that is under diagnosed, frequently overlooked,is often misdiagnosed and it is potentially fatal. A high index of clinical suspicion is required for correct diagnosis and timely intervention. To witness the event of embolism is extremely rare and is virtually confirmatory of the diagnosis. Here we present a case of a 56 years old male who was admitted to the emergency department with the diagnosis of Non-ST elevation myocardial infarction; the diagnosis was subsequently changed to pulmonary embolism when a thrombus-in-transit was witnessed on transthoracic echocardiography